Overexpression of plant uncoupling mitochondrial protein in transgenic tobacco increases tolerance to oxidative stress - Brandalise, M.; Maia, Ivan de Godoy [UNESP]; Borecky, J.; Vercesi, A. E.; Arruda, P. (Kluwer Academic/plenum Publ, 2003)
An Arabidopsis thaliana cDNA clone encoding a plant uncoupling mitochondrial protein (AtPUMP1) was overexpressed in transgenic tobacco plants. Analysis of the AtPUMP1 mRNA content in the transgenic lines, determined by Northern blot, revealed variable levels of transgene expression. Antibody probing of Western blots of mitochondrial proteins from three independent transgenic lines showed significant accumulation of AtPUMP1 in this organelle. Overproduction of AtPUMP1 in transgenic tobacco plants led to a significant increase in tolerance to oxidative stress promoted by exogenous hydrogen peroxide as compared to wild-type control plants. These results provide the first biological evidence for a role of PUMP in protection of plant cells against oxidative stress damage.
Keywords: transgenic tobacco; plant uncoupling protein; oxidative stress; constitutive overexpression